Effects of dexamethasone and oxidative environment on chondrogenesis of bone marrow-derived mesenchymal stem cells - Tangtrongsup, Suwimol, author; Kisiday, John, advisor; Frisbie, David, committee member; Goodrich, Laurie, committee member; Kipper, Matt, committee member (Colorado State University. Libraries, 2017)
Bone marrow-derived mesenchymal stem cell (MSCs) have received extensive consideration for applications to musculoskeletal tissue engineering based on their ability to differentiate into multiple skeletal lineage. For cartilage, MSCs-based therapies evaluated in vivo and in clinical studies have shown that MSCs can produce repair tissue that integrates with native tissue; however, defects remain partially cover, and the neotissue can contain fibrocartilage or evidence of hypertrophy. It is anticipated that a greater understanding of conditions that support MSCs chondrogenesis will lead to better results in cartilage tissue engineering. In chapter 1, fundamental aspects of MSCs including chondrogenesis and uses in tissue engineering are reviewed. Further, information regarding reactive oxygen species, and their involvement in the functioning of MSCs and chondrogenesis are presented. In chapter 2, MSC chondrogenesis was explored as a function of exposure to dexamethasone, anti-inflammatory glucocorticoid. Dexamethasone is known to support MSC chondrogenesis in vitro, although the effects of dose and timing of exposure are not well understood. Therefore, this study investigated these variables using a laboratory model of MSC chondrogenesis. In vitro MSCs chondrogenesis is conventionally induced in the presence of 100 nM dexamethasone; however, our result suggested that 1 nM dexamethasone was sufficient to supported robust cartilage-like ECM accumulation. By evaluating temporal exposure of MSCs to dexamethasone, we determined that exposure to dexamethasone during the first two days of culture was not critical, and that sustained exposure of at least a week appears to be necessary to maximize ECM accumulation. In chapter 3, we studied the oxidative environment associated with chondrogenic culture of MSCs. In conventional serum-free chondrogenic medium we noted that the concentration of intracellular reactive oxygen species (ROS) increased with time in culture. Previously, serum-free culture has been associated with increased ROS. Consistent with these reports, we found that supplementing chondrogenic cultures of MSCs with 5% fetal bovine serum reduced levels of intracellular ROS. Further, serum-supplementation increased the accumulation of collagen, a major component of cartilage extracellular matrix. Similar results were obtained using adult equine serum, which is as important as xenogeneic materials may be problematic for clinical applications. In summary, this study identified changes in the oxidative environment during MSC chondrogenesis, and suggested that lowering ROS may be an effective approach to increase collagen accumulation. In chapter 4, the extent to which reducing intracellular ROS can improve chondrogenesis was evaluated in a more precise fashion using antioxidants. To do so, we tested the effects of N- acetylcysteine (NAC), glutathione ethyl ester (GSHEE), or ammonium pyrrolidine dithiocarbamate (PDTC). First, we evaluate the effect of each antioxidant on intracellular ROS using DCFDA staining. We found that NAC and GSHEE were not effective in reducing intracellular ROS over time in our MSCs chondrogenic cultures. In contrast, PDTC decreased intracellular ROS and evidence of oxidative damage, while modestly increasing GAG accumulation. However, PDTC also moderately decreased the compressive stiffness of the MSC-seeded hydrogels. In summary, this study indicated that lowering ROS with specific antioxidants could enhance MSCs chondrogenesis, although loss of mechanical integrity is a major concern. The research described in this dissertation add to the knowledge of MSC chondrogenesis and the influences of dexamethasone and oxidative environment. We established that conventional doses of dexamethasone are at least a 100-fold higher than is necessary to support MSC chondrogenesis, which may be used to design dexamethasone delivery strategies to support MSCs chondrogenesis in vivo. During chondrogenesis, lowering levels of ROS that are encountered with conventional serum-free culture leads to higher levels of extracellular matrix accumulation. This information can be used to design in vitro or in vivo approaches to modulate the oxidative environment for optimal MSC chondrogenesis.
Keywords: chondrogenesis; extracellular matrix; reactive oxygen species; dexamethasone; antioxidant; mesenchymal stem cell